Patient self-care with double catheter lumen for hemodialization: validation of instructional folder - Maia, Sayonnara Ferreira; Facundes, Daniely Matias; Carneiro, Amanda Lorena Lima (Acta Scientiarum. Health Sciences, 2019)
The use of venous catheters for hemodialysis is associated with high rates of morbidity and mortality in patients with chronic renal failure. The implant of the dual lumen catheter (DLC) assists the patient in a worsening situation but commonly the patient remains with the DLC back home and this requires a series of important measures. The use of printed educational materials becomes an important tool to assist this type of care. Thus, the objective was to create and validate an instructive folder for the self-care of the patient using a catheter for hemodialysis. It is a methodological study of creation and evaluation of technology, in three stages. For validation of the content and style the material was submitted to the evaluation by experts in the area. 92.3% of the participants stated that the folder demonstrates clarity in their language, 53.8% of the participants suggested change and addition of information, and the same percentage also states that the instrument is attractive. The main suggestions were to change some term/word used in the folder, suggest changes to the images used, and include some information in the content. It is presumed then that the use of educational materials results in benefits to the patients who will receive the guidelines for self-care. Thus, the importance of nurses to use these resources for chronic renal patient care is emphasized.